Adjunct Language Instruction For English As a Second Language Engineering Students In The Writing Of Physics Laboratory Reports - Omar, Megawati (2005)
This study investigated the extent to which adjunct language instruction (ALI) was effective and identified the factors that influenced the effectiveness. In exploring the effectiveness, this study attempted a study on engineering students in UiTM using customized lab report writing instructional materials. A needs analysis was conducted and it showed that engineering students preferred learning report writing to personal essay writing. The students' preference for learning report writing set the stage for further exploration. Sixty students were instructed lab report writing in content-based writing using genre-based materials based on the students' actual Physics lab experiments, called Physics Adjunct Language Instruction (PALI). The results showed that the students' grades of lab report writing improved. Another test was carried out to find whether teaching writing in an ALI approach was able to meet the writing needs of engineering students. This test used Structural Equation Modeling (SEM) as an analytical tool. As SEM requires a sample size of 200 to 300 respondents, another instruction using similar materials, PALI, was carried out on 260 engineering students. The structural model showed that there were two factors that influence the improvement of the students' lab report writing in PALI. The factors were the teaching conduct and the preference for materials. In summary, the research revealed three main findings. First, the type of writing needed by engineering students in UiTM was report writing. Second, the PAL1 led to an improvement in the engineering students' lab report writing (t = -8.01, p = .000). Third, PAL1 provided two factors or conditions necessary for its success: the way the lab report writing was taught (/3= 0.451) and the preference of materials which are related to the learners' content subject (/3= 0.419). These two necessary conditions contribute 69.9 % (R* .699) to meeting the success in lab report writing of these engineering students